Aplicando a regra dos produtos notáveis , calcule :
a) (√5+√7)^2
b) (√5-√3)^3
c) (9+√21)x(9-√21)
d) (3√2+2√3)^2
e) (-11-√10)x(-11+√10)
Ajuda please
Soluções para a tarefa
Respondido por
3
a
(V5 + V7)² = (V5)² + 2 .V5.V7 + (V7)² = 5 + 2V35 + 7 = 12 + 2V35 ***
b
(V5 - V3)³ = (V5)³ - 3.(V5)² .V3 + 3.V5.(V3)² - (V3)³ = ( V5 )³ - 15V3 + 9V5 - (V5)³ =
( V5².V5 ) - 15V3 + 9V5 - ( V5².V5) = 5V5 - 15V3 + 9V5 - 5V5 = -15V3 + 9V5 ***
c
( 9 + V21) ( 9 - V21) = (9)² - (V21)² = 81 - 21 = 60 ***
d
( 3 V2 + 2V3)² = (3V2)² + 2.(3V2).(2V3) + ( 2V3)² = (9.2) + 12V6 + (4.3) = 18 + 12V6 + 12 = 30 + 12V6 ***
e
( -11- V10 ) ( - 11 + V10) = (-11)² - (V10)² = 121 - 10 = 101 ***
(V5 + V7)² = (V5)² + 2 .V5.V7 + (V7)² = 5 + 2V35 + 7 = 12 + 2V35 ***
b
(V5 - V3)³ = (V5)³ - 3.(V5)² .V3 + 3.V5.(V3)² - (V3)³ = ( V5 )³ - 15V3 + 9V5 - (V5)³ =
( V5².V5 ) - 15V3 + 9V5 - ( V5².V5) = 5V5 - 15V3 + 9V5 - 5V5 = -15V3 + 9V5 ***
c
( 9 + V21) ( 9 - V21) = (9)² - (V21)² = 81 - 21 = 60 ***
d
( 3 V2 + 2V3)² = (3V2)² + 2.(3V2).(2V3) + ( 2V3)² = (9.2) + 12V6 + (4.3) = 18 + 12V6 + 12 = 30 + 12V6 ***
e
( -11- V10 ) ( - 11 + V10) = (-11)² - (V10)² = 121 - 10 = 101 ***
ySennin4D:
mt obg
Perguntas interessantes
Filosofia,
11 meses atrás
Pedagogia,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás